CGMP-PKG dependent transcriptome in normal and degenerating retinas: Novel insights into the retinitis pigmentosa pathology. (November 2021) - Zhou, Jiaming; Rasmussen, Michel; Ekström, Per
Abstract: Retinitis Pigmentosa represents a group of genetic disorders that cause progressive vision loss via degeneration of photoreceptors, but there is in principle no treatment available. For any therapy development, a deeper comprehension of the disease-leading mechanism(s) at the molecular level is needed. Here we focused on the cGMP-PKG system, which has been suggested to be a driver in several models of the disease. To gain insights in its downstream signaling we manipulated the cGMP-PKG system with the aid of organotypic retinal explant cultures from either a mouse-based disease model, i.e. the rd1 mouse, or its healthy wild-type counterpart (wt), by adding different types of cGMP analogues to either inhibit or activate PKG in retinal explants from rd1 and wt, respectively. An RNA sequencing was then performed to study the cGMP-PKG dependent transcriptome. Expression changes of gene sets related to specific pathways or functions, that fulfilled criteria involving that the changes should match PKG activation and inhibition, were determined via bioinformatics. The analyses highlighted that several gene sets linked to oxidative phosphorylation and mitochondrial pathways were regulated by this enzyme system. Specifically, the expression of such pathway components was upregulated in the rd1 treated with PKG inhibitor and downregulated in the wt with PKG activator treatment, suggesting that cGMP-PKG act as a negative regulator in this context. Downregulation of energy production pathways may thus play an integral part in the mechanism behind the degeneration for at least several RP mutations. Highlights: cGMP-PKG dependent transcriptome. cGMP-PKG system affects photoreceptors' death. cGMP-PKG system negatively regulates oxidative phosphorylation and mitochondrial pathways at the transcriptional level, which may affect retinal degeneration.